ANALISIS MINAT BELI FASHION MUSLIM PADA MAHASISWA UIN WALISONGO SEMARANG MELALUI APLIKASI LAZADA - Zaharo , Diana Nur; Lafiah , Lafiah; Izza Hafida Milla , Ghifarina; Fahmy , Zulfa; Zikrinawati , Khairani (Investama : Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the intention to buy Muslim fashion among UIN Walisongo Semarang students through the Lazada application. This research was conducted using a descriptive qualitative approach. Descriptive qualitative research focuses on extracting data by using interviews through Google meet with the subjects to collect in-depth information regarding consumer preferences and needs through focus group discussions. The results of the study show that UIN Walisongo students have a high interest in buying Muslim fashion through the Lazada application. This can be seen from the positive responses given by respondents during interviews conducted through Google Meet. Respondents stated that they often use the Lazada application to buy Muslim fashion. Students, most of whom are young people, are more interested in trending things, namely keeping up with the times (updating). They are interested in wearing any trending fashion so that they appear confident when wearing trending fashion